Trienzyme과 Lactobacillus casei를 이용한 국내 수산 자원의 엽산 분석 및 유효성 검증 - 정보미(Bomi Jeong); 남기호(Ki-Ho Nam); 김연계(Yeon-Kye Kim); 천지연(Jiyeon Chun) (한국식품과학회지, 2020)
Fishery resources have been widely consumed as protein- and vitamin-rich food sources in the Korean diet. However, information regarding their vitamin levels is extremely limited. In this study, trienzyme-Lactobacillus casei method was validated and used to determine the folate contents in fishery foods. The trienzyme-L. casei method for folate analysis showed excellent accuracy (85.2 to 95.3% recovery) and precision (repeatability 1.4% RSD and reproducibility 2.4% RSD). Folate contents of 20 fish foods (4 fish, 3 crustaceans, 3 sea algae, 3 cephalopods, 4 shellfish, and 3 others) ranged from 1.75 to 97.98 ㎍/100 g. Furthermore, we found that the folate content in seaweed fusiforme was the highest, followed by gulfweed (69.73 ㎍/100 g). Folate analysis using the trienzyme-L. casei method was determined excellent based on the z-score of -0.3 in the Food Analysis Performance Assessment Scheme test. Analytical and method validation data generated in this study could be used to update the national food composition table on vitamin B9 in Korean fishery resources. 본 연구에서는 trienzyme 추출 및 L. casei 분석법을 국내 다양한 수산 자원의 엽산 분석에 적용하기 위해 분석수행지표(직선성, 민감성, 정확성, 정밀성)를 분석 평가하여 분석법의 유효성을 검증하였다. 분석법의 검출한계(LOD)와 정량한계(LOQ)는 각각 0.562 ㎍/100 g와 1.057 ㎍/100 g으로 엽산 함량이 낮은 식품에 적용할 수 있는 분석법으로 나타났다. 시료 중 엽산 함량에 대한 L. casei 생육 관계는 다항식 모델(y=4-1.132/((1+X/0.0502)1.02)+1.26)로 분석한 결과 R2=1.0000을 나타내는 우수한 상관성을 얻었다. 또한, 분석법의 정확성과 정밀성이 우수한 수준임을 확인할 수 있었으며, 수산 자원 6개 군별에 따른 엽산 회수율 분석에서도 약 87-108%의 신뢰도가 확보된 회수율을 나타냄을 확인하였다. 본 연구에서 분석한 수산자원 20종의 엽산 함량분석 및 검증 데이터는 국내 수산 자원에 대한 신뢰도 있는 데이터베이스 구축 자료로 활용될 수 있을 것으로 판단되며, 한국은 삼면이 바다로 인접된 지리적 특성으로 인하여 일상 식단에서 다양한 수산 자원이 자주 이용되고 있는 바 trienzyme-L. casei 분석법을 향후 수산 자원의 엽산 함량 분석에 확대 적용하여 국가수준의 영양성분데이터베이스 구축에 기여할 수 있을 것이라 사료된다.